Performance of concrete by using pulverized fuel ash (PFA) as a cement replacement material - Noor Faddly , Mohamad (2010)
Through public concerns and research efforts, the coal combustion by-product materials have potential to be utilized as construction material to replace conventional ordinary Portland cement (OPC). Recycling the coal combustion byproduct materials is the act of processing the waste material to creating an alternative product. The used of pulverized fuel ash (PFA) as a pozzolanic material as a partial cement replacement for producing concrete will reduce the environmental pollution problems create by excessive production of cement, as well as the requirement for disposing the ash. Mix design facilitates the percentage used of pulverized fuel ash (PFA) concrete assessed together with the aggregates and cement. In this present investigation, PFA concrete is mix according to 10%, 20% and 30% by weight of cement replaced with PFA. The present study designed to determine the effectiveness of PFA and discovered its potential as a partial cement replacement in concrete. It is also to study the effectiveness of PFA concrete toward compressive strength and durability in term of increasing its resistance toward chemical attacks namely sulphate and acid. The continuation of pozzalanic activity in PFA concrete would reduce the porosity of concrete at 90 days of curing age. The entire PFA concrete specimens prepared consist of PFA-20% as partial cement replacement material indicates the optimum usage of PFA. Conclusively, the introduction of PFA as cement replacement in concrete as an alternative material would improve the properties of PFA concrete.